Introduction: Restoration of the National Defence in Estonia – from Scrambled Eggs Back into the Shell - Velliste, Trivimi (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2014)
I compare the three Baltic States to three eggs. Colourful metaphors are sometimes necessary to gain a better understanding of historical events. It is easy to make scrambled eggs from an egg, but it’s a lot more difficult, seemingly impossible, to unscramble the eggs and put them back into a living egg inside a protective shell. But that’s exactly what happened with Estonia, Latvia and Lithuania in the 20th century.